Kadar Fosfor (P) dalam Cairan Sulkus Gingiva pada Penderita Periodontitis Kronis (Phosphorus Level of Gingival Crevicular Fluid of Chronic Periodontitis) - Deasy Kusuma Ardiani; Agustin Wulan Suci Dharmayanti; Peni Pujiastuti (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Background: The prevalence of periodontal disease in Indonesia is 60%. Chronic periodontitis is one of periodontal disease which affects Indonesian. The primary cause of periodontal disease is bacterial plaque. Adhesions and accumulation of bacterial plaque can cause inflammation and destruction of periodontal tissue following by increasing of gingival crevicular fluid flows and releasing of its components, one of the components is phosphorus that excreted from sulcular epithelium. Soluble phosphorus along blood stream is from gingival crevicular fluid which the flow is increased and excreted by sulcular epithelium. Objective: To know phosphorus levels in the gingival sulcus of chronic periodontitis. Methods: The subjects of the study were patients who came to the Dental Hospital University of Jember and occupied as inclusion and exclusion criteria. The subjects who had inclusion criteria were divided into 2 groups based intra-oral examination; gingivitis and chronic periodontitis. Gingival crevicular fluid sampling was taken from tooth with gingivitis or chronic periodontitis using paperpoint. Phosphorus level measurement used UV-Vis Spectrophotometer with a wavelength of 883 nm. The results were analyzed by Mann-Whitney test. Results: There were phosphorus in the gingival crevicular fluid of chronic periodontitis and it higher than gingivitis. Conclusion: There is phosphorus level in the gingival crevicular fluid in patients with chronic periodontitis. Keywords: Chronic periodontitis, gingival crevicular fluid, phosphorus